Measuring the Maghreb: What do rankings and indexes really tell us? - Aljoscha Albrecht; Isabelle Werenfels (Stiftung Wissenschaft und Politik (SWP), 2021)
International rankings and indexes, such as the World Press Freedom Index published in mid-April 2021, are increasingly influential in the Maghreb. The region's governments promote improvements in their own performance, protest where they score poorly, and celebrate outranking their rivals. Rankings also allow opposition groups and activists to spotlight grievances in their own country. External cooperation partners, above all the European Union (EU) and its member states, use them as a basis for decision making and policies towards Algeria, Morocco and Tunisia. While rankings and indexes insinuate objectivity and comparability, their sources, validity and utilisation are frequently problematic. Only if they are embedded in qualitative research on the Maghreb and their downsides reflected can they make a meaningful contribution to identifying reform needs and addressing deficits.
Keywords: 320